Implementation of Worship and Religious Preservation Obligations in Inpatients at YARSI Hospital - Nidya Rhenatama Angelia; Rifqatussa'adah Rifqatussa'adah; Fathul Jannah (Junior Medical Journal, 2023)
According to WHO, healthy involves a state of complete well-being which includes four dimensions: physical, mental, social and spiritual. A person's level of spirituality can affect his quality of life. In relation to the healing process, spirituality can be explained by holistic concepts and services in nursing. YARSI Hospital itself has conducted an assessment of the spiritual aspect among other Islamic hospitals entitled "Spiritual Friendly" or can be mentioned with its motto that preserves religion (hifdz Addin), such as the obligation of worship and religious preservations obligations. This study aims to find out an overview of the implementation of spiritual aspects in inpatients at YARSI Hospital and its review in Islam. This study used analytical survey research with a cross-sectional research design. The sample was established using purposive sampling technique. The population of this study was inpatients at YARSI Hospital for the period of May – December 2021 with its collection using the YARSI Hospital Information System instrument with a sample of 1703 patients. The results showed that the majority of patients were women. The results of the statistical test also showed that gender was related to worship obligations (p=0.003) and religious actions (p=0.000), age with religious actions (p=0.000), length of hospitalization with worship obligations and religious actions (p=0.000). Meanwhile, at the age of worship obligations, no significant relationship was found. The conclusion in this study is that the nature of disease in Islam is the best test given by Allah Almighty. A good believer when given an exam will have to respond sincerely, patiently, and seek treatment.